Electrical Energy Audit at The Syekh Yusuf Regional Hospital Gowa Regency - Iswan, Nur Fadilah; Zulhajji, Zulhajji; Haripuddin, Haripuddin (Teknik Elektro, Universitas Negeri Makassar, 2025)
This study aims to determine: (1) the amount of electricity consumption in the laboratory building, radiology building, and blood transfusion unit building. (2) the results of energy audits in the laboratory building, radiology building, and blood transfusion unit building at the Syekh Yusuf Regional General Hospital, Gowa Regency and to analyze energy saving opportunities that can be applied to the building. This study uses a quantitative descriptive method. The data collection techniques used are documentation, observation and measurement. In this study, the researcher analyzed the data descriptively and provided a general description of the electricity Energy Consumption Intensity (IKE) using statistical analysis techniques. The results of this study indicate (1) the large consumption of electrical energy in the 197,000 VA laboratory building with an average IKE value in the building of 55.325 kWh/m2, the 41,500 VA radiology building with an average IKE value in the building of 50.3187 kWh/m2, and in the 23,000VA blood transfusion unit building with an average IKE value in the building of 176.02 kWh/m2. (2) As well as knowing the results of the energy audit in the laboratory building, the load that uses the most electrical energy is 1 PK AC 3,097.6 kWh, in the radiology building which uses the largest electrical energy is 1,536 kWh, and in the blood transfusion unit building which uses the largest electrical energy is 176.64 kWh. Based on the analysis of electrical energy opportunities at the Syekh Yusuf Regional General Hospital, Gowa Regency, three saving efforts were obtained, namely no-cost, low-cost, and high-cost opportunities.